2012
DOI: 10.1007/s13224-012-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Gravidogram and Ultrasound in Detection of IUGR

Abstract: Objectives The present study was conducted to compare the gravidogram and ultrasound in the detection of intrauterine growth restriction. Methods This study was conducted in the Department of Obstetrics and Gynecology, Voluntary Health Services, Chennai (TN) from August 2007-May 2009. The study included 321 women with singleton pregnancy in a longitudinal lie. These women underwent serial symphysiofundal height measurements and ultrasound. Birth weights of the newborns were noted at the time of delivery. Gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…Present study is comparable to the study conducted by Pillay P et al who in their study found that detection of IUGR by USG had a sensitivity of 85.2%, specificity of 96.6% and PPV of 83.6% and NPV of 97%. 8 Present study was contrary to that of Baschat and Weiner. 13 In their study, they showed that low abdominal circumference percentile had the highest sensitivity (98.1%) for diagnosing IUGR.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Present study is comparable to the study conducted by Pillay P et al who in their study found that detection of IUGR by USG had a sensitivity of 85.2%, specificity of 96.6% and PPV of 83.6% and NPV of 97%. 8 Present study was contrary to that of Baschat and Weiner. 13 In their study, they showed that low abdominal circumference percentile had the highest sensitivity (98.1%) for diagnosing IUGR.…”
Section: Discussioncontrasting
confidence: 99%
“…Pillay P et al in their comparative study of Gravidogram and USG in diagnosing IUGR found that when both these modalities were used together, it reduced the sensitivity to 31.4% but increased the specificity to 98.8%, PPV to 92.5% and NPV to 98%. 8 Pearce JM et al in their comparative study of SFH and USG also concluded that screening from both the tests improved the sensitivity to 93%, reduced specificity to 67% and had a PPV of 32%. 14 The study reflected following facts:…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Incidence of low birth weight babies is 16.8% in some studies in India. 15 Primiparity is an independent risk factor for intrauterine growth restriction. 16 This coincides with our present study analysis where most pregnant women with IUGR were primigravidae (72%).…”
Section: Discussionmentioning
confidence: 99%
“…Though in our study, the incidence of preterm labour was significantly more than controls (7.6% vs. 1.1%), it is not appreciably more than the general incidence of preterm labour (11.1%) [16]. The reported national incidences of hypertensive disorders of pregnancy (10.08%) [17], Gestational Diabetes (13.4%) [18], Anemia complicating pregnancy (50%) [19], placenta previa (1.01%) [20], IUGR (16.8%) [21], Low Birth Weight (20%) [22], Birth asphyxia (6%) [23], are relatively higher, compared to the statistics in maternal subclinical hypothyroidism, meaning that subclinical hypothyroidism with normal free T3 and T4 levels may not significantly contribute to the incidence of above-mentioned complications.…”
Section: Discussionmentioning
confidence: 99%